Miniaturised Marine Algae Test with Polycyclic Aromatic Hydrocarbons − Comparing Equilibrium Passive Dosing and Nominal Spiking - Nora Claire Niehus and Carolin Floeter and Henner Hollert and Gesine Witt (Aquatic Toxicology, 2018)
In this study the miniaturised Marine Algae Test (mMAT) using passive dosing was developed based on the ISO EN DIN10253 to investigate the growth inhibition of the marine diatom Phaeodactylum tricornutum caused by polycyclic aromatic hydrocarbons (PAHs). Risk assessment of hydrophobic organic compounds (HOCs) like PAHs in aquatic toxicity tests is very difficult due to their low aqueous solubilities, losses via sorption to the wells and volatilisation. However, passive dosing can overcome these challenges. In this study biocompatible silicone O-rings were used as PAH reservoir. Individual PAHs at saturation were tested using passive dosing and in comparison with nominal spiking. Additionally, a recreated mixture of PAHs reflecting the field composition of the sediment pore water was tested with passive dosing. PAHs revealed strong growth inhibiting effects on algal growth in passive dosing tests, while nominal spiking had only slightly growth inhibiting effects in the highest concentration. The recreated PAH mixture revealed slightly inhibiting effects using passive dosing when tested with a factor of 5000 of the field concentration. This study demonstrates the superiority of passive dosing to spiking and further the successful implementation of passive dosing in the marine algae test maintaining a constant concentration for HOCs with a log KOW?>?4.6.
Keywords: growth inhibition; marine algae; mixture toxicity; PAHs; passive dosing; spiking